Suap Menyuap dalam Perspektif Pasal 2 & 3 UU Nomor 11 Tahun 1980 tentang Tindak Pidana Suap dan Hadits Riwayat Ahmad - Azizah, Wardatul; Arifin, Tajul (Afkaruna: International Journal of Islamic Studies (AIJIS), 2024)
The crime of bribery and criminal acts of corruption are disgraceful acts related to abuse of position, discriminatory behavior by giving special privileges to someone based on receiving bribes or rewards, violating public trust so that democracy is damaged, damaging the mentality of officials in both the private corporate sector and the government sector, endanger the security of society at large, and cause competition in business to be flawed or unfair. Based on reports and surveys from GCB in 2020, the level of bribery practices in Indonesia was in the third highest position out of 17 Asian countries. The aim of this research is to determine bribery from the perspective of Law Number 11 of 1980 and based on the Hadith History of Ahmad. Researchers utilize a descriptive approach in qualitative research methods, using primary and secondary data as sources of information. Based on the Hadith perspective, Ahmad's history says that Allah SWT and the Prophet Muhammad SAW will curse the bribe recipients, bribe givers and intermediaries.